(untitled) (Research, Society and Development, 2022)
Objectives: The present study aimed to evaluate the main pathologies of patients followed up in the palliative care service of a university hospital. METHODS: A retrospective cohort study involved 153 palliative care patients, aged 4 months to 95 years, hospitalized from January 2020 to August 2021. Clinical, biochemical and radiological data were collected from the patients’ medical records. Results: According to the data analyzed during hospitalization, the mean age is 66.78 years, with about 2 different diagnoses or clinical conditions. Most patients (about 24.18%) had sexually transmitted diseases, followed by patients with neoplasms (22.22%), vascular diseases (16.99%), neurodegenerative diseases (4.57%), liver diseases (3.26%) renal failure (9.80%), lung diseases (16.99%) and malformations (0.65%). Conclusion: The present study is in accordance with the new WHO update, in which palliative care is offered to all patients with chronic diseases, with cancer patients occupying second place in the pathological frequency.